Assessing and Managing Security Risk in IT Systems - McCumber, John (Auerbach Publications, 2004)
This book begins with an overview of information systems security, offering the basic underpinnings of information security and concluding with an analysis of risk management. Part II describes the McCumber Cube, providing the original paper from 1991 and detailing ways to accurately map information flow in computer and telecom systems. It also explains how to apply the methodology to individual system components and subsystems. Part III serves as a resource for analysts and security practitioners who want access to more detailed information on technical vulnerabilities and risk assessment analytics. McCumber details how information extracted from this resource can be applied to his assessment processes.